Analysis of the efficacy of frenotomy in the treatment of difficulty in breastfeeding caused by the lingual frenum - Vasconcelos, Raquel Lopes Pinto; Magalhães, Ataydes Dias (Seven Editora, 2023)
Introduction: The lingual frenum is a mucous membrane that connects the tongue to the oral floor, it is responsible for the free movement of the tongue in the mouth. The altered lingual frenulum can be responsible for several problems for the newborn, including difficulties to perform functions such as sucking and swallowing, as well as impairing the proper grip of the breast during breastfeeding, which can cause pain in the mother and difficulties for the baby such as gaining weight and early weaning. Phrenotomy is a simple surgical procedure that has been employed as a treatment option for lingual frenulum alteration, with the aim of improving the condition and quality of life of the mother and newborn in the context of breastfeeding. Objective: To analyze the efficacy of frenotomy in the treatment of difficulty in breastfeeding caused by the lingual frenum, based on a review of the available medical literature on the subject. Clinical studies, such as literature reviews, case reports and research on this topic will be evaluated, in order to identify the evidence on the efficacy and safety of this procedure, pointing out the improvements identified after surgery. Literature review: It is important to identify changes in the lingual frenulum, as they negatively affect the patient’s quality of life. Therefore, it is crucial to carry out an early diagnosis in order to offer the most effective treatment for this problem. For this, it is essential that professionals have adequate knowledge to make an accurate diagnosis and solve the issue. Phrenotomy is an option to be considered due to its simplicity in clinical and surgical practice, in addition to presenting few risks in the postoperative period. Final considerations: Given that the initial phase of breastfeeding is crucial for the health and quality of life of the baby, phreotomy is a safe and effective treatment, which also avoids or decreases the consequences of long-term lingual frenulum alteration. Even though there is still research that reports that it is a temporary improvement, this improvement is quite necessary to prevent early weaning, thus avoiding weight loss and the difficulty that mothers face to maintain breastfeeding. DOI:https://doi.org/10.56238/innovhealthknow-008